ANALYSIS OF FISHERY BIOECONOMIC IN THE EAST COASTAL OF BINTAN ISLAND - yudi wahyudin (Universitas Djuanda, 2018)
The objective of this study is to measure the potential economic value of fisheries in the area of conservation of seagrass meadows on the eastern coast of Bintan island. The result of this study could became a policy input for managing sustaibale fisheries resources. The presence of seagrass ecosystem could support carrying capacity of the surrounding area of seagrass for growing related biotas that associated with the seagrass ecosystem. The number of benefit of seagrass ecosystem could be measured by production surplus approach. The result of analysis shows that the economic value of fisheries of seagrass ecosystem is equal to the fisheries economic IDR 92.73 billion or IDR 558.28 million hectare-1 year-1 in 2016. The maximum economic yield (MEY) of this artisanal fisheries is 5032 ton year-1 with the number of effort should be maintained at 5281 trip of net fishing gear. A sustainable fisheries management should be maintained in the level of harvest and effort in MEY condition in order to give a maximum benefit to the fishermen and sustaible to the fisheries. Keywords: seagrass ecoystem, seagrass fisheries, bioeconomic of seagrass fisheries, eastern coast of Bintan island, maximum economic yield